2022
DOI: 10.3390/pharmaceutics14030620
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetic Assessment of Kratom (Mitragyna speciosa), a Botanical Product with Opioid-like Effects, in Healthy Adult Participants

Abstract: Increasing use of the botanical kratom to self-manage opioid withdrawal and pain has led to increased kratom-linked overdose deaths. Despite these serious safety concerns, rigorous fundamental pharmacokinetic knowledge of kratom in humans remains lacking. We assessed the pharmacokinetics of a single low dose (2 g) of a well-characterized kratom product administered orally to six healthy participants. Median concentration-time profiles for the kratom alkaloids examined were best described by a two-compartment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 28 publications
2
50
1
Order By: Relevance
“…7HMG content in the dosed kratom product was below the LLOQ, but 7HMG formed after metabolism of mitragynine was quantified in plasma samples, and metabolite to parent exposure ratio ((AUC 7HMG / AUC mitragynine ) × 100) was 26.5%. 5 Corynantheidine was not specifically investigated in this clinical study, but it was one of four alkaloids (mitragynine, 7-hydroxymitragynine, and speciociliatine) available systemically after oral doses of either lyophilized kratom tea or a commercial kratom product (OPMS) in male rats. 2…”
Section: ■ Kratom Pharmacokineticsmentioning
confidence: 99%
“…7HMG content in the dosed kratom product was below the LLOQ, but 7HMG formed after metabolism of mitragynine was quantified in plasma samples, and metabolite to parent exposure ratio ((AUC 7HMG / AUC mitragynine ) × 100) was 26.5%. 5 Corynantheidine was not specifically investigated in this clinical study, but it was one of four alkaloids (mitragynine, 7-hydroxymitragynine, and speciociliatine) available systemically after oral doses of either lyophilized kratom tea or a commercial kratom product (OPMS) in male rats. 2…”
Section: ■ Kratom Pharmacokineticsmentioning
confidence: 99%
“…There is also a severe lack of studies investigating the pharmacokinetics of MG in humans, with only two published to date. The first of which was conducted in male subjects only, while the second included four female subjects but statistical analysis between male and female participants were not reported (Tanna et al, 2022;Trakulsrichai et al, 2015). Given the lack of pharmacokinetic studies and the variability in kratom product selection and preparation, it is difficult to form any conclusions on how the kinetics of MG and other kratom alkaloids may contribute to individual differences in behavioral responses such as mechanical hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic and Pharmacodynamic Consequences of CYP3A Inhibition on Mitragynine Metabolism in Rats. Kamble et al kratom alkaloids after an oral dose of kratom tea; in that study mitragynine showed fast absorption (T max , 1 hr) with an elimination half-life of 45.3 h (Tanna et al, 2022).…”
mentioning
confidence: 98%
“…The opioidergic activity of kratom is often attributed to its most abundant bioactive alkaloid mitragynine and its metabolite, 7-hydroxymitragynine (7HMG). Mitragynine is reported to be 66% of the total alkaloidal fraction of kratom, whereas 7HMG analyzed in freshly prepared extracts are below the lower limit of quantification (0.01 %w/w), suggesting 7HMG is not biosynthesized in Mitragyna leaves (Hassan et al, 2013;Singh et al, 2020;Tanna et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation